The Association of Serum Irisin with Bone Mineral Density and Turnover Markers in New-Onset Type 2 Diabetic Patients. (28th February 2022) - Wang, Xiujing; Hu, Tianxiao; Ruan, Yun; Yao, Jiaqi; Shen, Huiling; Xu, Yao; Zheng, Bojing; Zhang, Zhengying; Wang, Jing; Tan, Qingying
Abstract : Background . Irisin, an exercise-induced myokine and adipocytokine, has been reported to decrease in type 2 diabetic patients. Recently, several research studies indicated that circulating levels were correlated with bone mineral density (BMD). To evaluate bone metabolism, bone turnover markers (BTMs) should be included. However, with respect to newly diagnosed T2DM patients, the relevance of their irisin levels to their BTMs and BMD remains unclear. The investigation of serum irisin levels in patients who have been newly diagnosed with type 2 diabetes and illumination of the relationship between serum irisin levels and those two indices of BMD and BTMs mentioned above are the intention of this cross-sectional study. Methods . 66 new-onset type 2 diabetic patients (T2DM group), together with 82 control subjects (NGT group), were recruited in this study. Serum irisin concentrations and BTMs (including osteocalcin (OC), procollagen type 1 N-terminal propeptide (P1NP), and β -C-terminal telopeptides of type I collagen ( β -CTX)) were determined by the enzyme-linked immunosorbent assay (ELISA). Glucose, lipid profile, and insulin were considered as measuring indicators as well. Dual-energy X-ray absorptiometry (DXA) was utilized to evaluate the indicator of BMD. Serum irisin, BTMs, and BMD were compared between diabetic patients and healthy individuals. Pearson and Spearman correlation analyses were applied as well to assess correlations between irisin and BTMs and BMD. Multiple stepwise regression analysis was conducted to identify the independent factors of irisin. ROC curve analyses were carried out for serum irisin prediction for osteoporosis/osteopenia (OP). Results . The serum levels of irisin, procollagen type 1, intact N-terminal propeptide (P1NP), and osteocalcin (OC) were evidently lower in T2DM subjects than in NGT subjects (10.90 ± 1.88 vs .11.69 ± 2.06 ng/mL, P  < 0.05; 36.42(25.68, 51.70) vs. 44.52(35.73, 58.05)ng/ml, P  < 0.05; 16.15(12.40, 21.66) vs. 18.70(15.56, 23.22)ng/ml, P  < 0.05). Among patients with T2DM, the circulating irisin level of those with OP was lower than that of normal BMD (9.98 ± 2.09 vs. 11.39 ± 1.57 ng/ml, P  < 0.01); irisin had a negative correlation with β -C-terminal telopeptides of type I collagen ( β -CTX) ( r  = −0.496, P  < 0.001) and came back unrelated to Lumbar BMD; Lumbar BMD was negatively relevant to OC ( r  = −0.274, P  < 0.05) and β -CTX ( r  = −0.410, P  < 0.01). Multiple linear regression analyses of stepwise models implied that TG, LDL-C, and β -CTX were independently associated with serum irisin concentrations (P  < 0.01 or P  < 0.05). Conclusion . Serum irisin level was declined in patients with type 2 diabetes diagnosed in the near term and had a certain association with bone turnover markers. It is suggested to consider irisin as a potential biomarker of bone metabolic disorder in T2DM patients with the initial diagnosis.